In Bangladeshi Female Cadaver, the Change of Outer Diameter of the Infundibulum of Fallopian Tube in Advancing Age (Update Dental College Journal, 2018)
Context: Problems with the fallopian tubes can lead to infertility. Disease can be defined and measured only in terms of deviation from normal structure. Detailed morphological and histological knowledge is essential for the diagnosis and management of fallopian tube disease.Objectives: To identify the outer diameter of the infundibulum and its changes with advancing age.Study Design: Cross sectional descriptive type of study.Period and place: Department of anatomy, Dhaka Medical College from July 2008 to June 2009.Materials: Present study was performed on post mortem fallopian tubes of 60 Bangladeshi female. Among them lowest age was 12 years and highest age was 50 years.Methods: Samples were divided into three differential age groups: Group A (10-13 years), Group B (14-45 years), Group C (46-50 years). All samples were studied morphologically and histologically.Results: The mean outer diameter of the infundibulum of the right and left fallopian tubes ranged from 0.80±0.01 to 1.03±0.22 mm. The difference between all the groups were statistically significant (p < 0.001).Conclusion: There was change in outer diameter of the infundibulum of fallopian tubes of left and right in relation to age.Update Dent. Coll. j: 2018; 8 (2): 23-25